4CPS-271 Development of pharmacist medication review in paediatric discharge process. (March 2019) - Solano, M; Jeannin, M; Anxionnat, R; Clairet, AL; Limat, S
Abstract : Background: Paediatric patients need follow-up during discharge as they are at higher risk of medication errors owing to complex medical care. Purpose: This study aimed to assess the frequency and type of pharmacist interventions during medication review at paediatric transition from hospital to home. The second aim was to assess patients' comprehension and satisfaction. Material and methods: This was a prospective pilot study conducted by the pharmacy department in a paediatric unit. A pharmacist provided discharge counselling for patients with chronic diseases and introduction or change of treatment during hospitalisation. He conducted follow-up telephone encounters between day 3 and day 7 post-discharge. The number and type of pharmacist interventions and physician acceptance rates were assessed. Patients' comprehension and need for further information were compared before and after pharmacist medication review. The time to obtain treatment after discharge was reported. Patients' satisfaction was identified. Results: There were 41 pharmacist medication reviews during the 7 month study. A pharmacist was able to provide discharge counselling for 49% of discharges. The pharmacist identified 23 interventions, of which 87% were accepted and 13% were informational in nature. The most frequently identified interventions included dosage form optimisation and administration optimisation. An average of patients' knowledge self-assessment was 5.8/10 and 8.6/10 before and after pharmacist discharge counselling, respectively. Patients needed further information concerning administration and side effects for 71% and 51% before pharmacist discharge counselling, respectively. After pharmacist discharge counselling, they needed this information for 5% and 7%, respectively. Seventy-eight per cent of patients could get their treatment without delay after discharge. Eighty-three per cent of patients recommended this type of pharmacist medication review (17% not provided). Conclusion: Pharmacists can provide a valuable service in patients' management during childrens' discharge process by detecting prescription errors, optimising administration and counselling patients. Facilitating the discharge process satisfies patients and can help to provide continuity of care. References and/or acknowledgements: No conflict of interest.